A network reconfiguration algorithm for the reduction of expected fault currents - Vovos, Panagis N.; Hwachang Song; Kang-Wook Cho; Tae-Sun Kim (Proceedings / IEEE Power Engineering Society General Meeting, 2013)
Aim of this work is to present an algorithm that could assist system operators facing higher fault levels than protection equipment can handle. The algorithm seeks an optimum system operating point, subject to operating and Fault Current Constraints (FCCs). This is achieved by an enhanced Optimal Power Flow (OPF) considering both traditional operating constraints and FCCs (FCC-OPF), up to the point this is adequate under the current network configuration, or suggests reconfiguration Remedial Actions (RAs) and then seeks the optimum operating point under the new network configuration. The FCC-OPF is presented in previous work, but here its application is extended. In this paper, we analyze a concise method for the identification of infeasible RAs, filtering of inadequate RAs for the reduction of fault currents below FCCs and ranking of RAs according to economy. The algorithm was tested on a medium-scale network and the results demonstrate efficiency for the suggested approach.